1996
DOI: 10.1164/ajrccm.153.3.8630581
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled bronchodilators reduce dynamic hyperinflation during exercise in patients with chronic obstructive pulmonary disease.

Abstract: Dynamic hyperinflation (DH) is a major pathophysiologic consequence of airflow limitation during exercise in patients with chronic obstructive pulmonary disease (COPD) and an important contributing factor to breathlessness. In this study we aimed to examine the effect of inhaled beta agonist therapy on DH during exercise in these patients and the relationship between changes in DH and breathlessness. In 13 COPD patients (mean age 65.1 +/- 2.0, FEV1 1.20 +/- 0.17, FEV1/FVC 40 +/- 3) we measured pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
226
0
16

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(259 citation statements)
references
References 25 publications
(57 reference statements)
17
226
0
16
Order By: Relevance
“…In keeping with numerous previous bronchodilator studies, the FEV1/FVC ratio was unchanged, indicating that increases in FEV1 were mainly the result of volume recruitment [2,3,[23][24][25].…”
Section: Effect Of Salmeterol On Resting Lung Volumessupporting
confidence: 88%
See 1 more Smart Citation
“…In keeping with numerous previous bronchodilator studies, the FEV1/FVC ratio was unchanged, indicating that increases in FEV1 were mainly the result of volume recruitment [2,3,[23][24][25].…”
Section: Effect Of Salmeterol On Resting Lung Volumessupporting
confidence: 88%
“…Bronchodilator-induced lung deflation reduced mechanical restriction, increased ventilatory capacity and decreased respiratory discomfort, thereby increasing exercise endurance. Several recent studies have shown that improvements in exertional dyspnoea following bronchodilator therapy in chronic obstructive pulmonary disease (COPD) correlate well with reductions in lung hyperinflation, as indicated by increases in inspiratory capacity (IC) [1][2][3][4][5]. However, the relationship between bronchodilator-induced increases in IC and improvements in symptoms and exercise performance is complex and poorly understood.…”
mentioning
confidence: 99%
“…These symptomatic improvements are associated with decreases in functional residual capacity (FRC) and residual volume (RV) and with increases in FVC, SVC, inspiratory capacity (IC) and specific conductance. RV was the most frequently reduced lung volume [18,22,25,[29][30][31]. The decrease in FRC means that end-expiratory lung volume decreased and that tidal breathing had moved to a lower operational lung volume.…”
Section: Discussionmentioning
confidence: 99%
“…A BDinduced increase in the resting IC (indicating reduced lung hyperinflation) in the order of 0.3 L or ,10% predicted, appears to be clinically meaningful and corresponds to important improvements in exertional dyspnoea and exercise endurance [3][4][5][16][17][18][19]. Several studies have shown that BD therapy does not alter the rate of dynamic hyperinflation (or air trapping) during exercise [3][4][5][16][17][18][19][20].…”
mentioning
confidence: 95%
“…EFFECT OF BDs ON DYNAMIC VENTILATORY MECHANICS DURING EXERCISE Improvements in resting inspiratory capacity (IC) have been shown to occur as a result of treatment with all classes of BDs and this indirectly signifies reduced EELV [3,[16][17][18]. A BDinduced increase in the resting IC (indicating reduced lung hyperinflation) in the order of 0.3 L or ,10% predicted, appears to be clinically meaningful and corresponds to important improvements in exertional dyspnoea and exercise endurance [3][4][5][16][17][18][19].…”
mentioning
confidence: 99%